(untitled) (Revista científica Olimpia, 2024)
Playing soccer is an eminently tactical sport, hence the need for players to relate to each other in order to organize themselves collectively and effectively in offensive and defensive situations, from which the rest of the technical, physical, theoretical and psychological capabilities will emerge. In research carried out, framed in the process of tactical preparation in soccer, there have been many ideas and research that have contributed to achieve important sports results, and that serve as the basis for the tools presented in this article, based on contemporary tactical training systems aimed at improving the tactical actions of the players. The objective of this work is to show a systematization of tactical preparation in soccer based on the principles and contextual foundations of modern training. This review contributes to enrich the levels of knowledge of coaches, which will therefore be reflected in the behavior of players in the four moments of soccer games according to the game model used. With this study the whole process of the organization of the work is visualized with which it was possible to determine the contents that are exposed as results, as well as a series of dimensions and indicators that allow evaluating the action of the performance of the tactical preparation of the players.